The Influence of Flexible Work Arrangements and Work-Life Balance on Employee Performance Among Lecturers at Public Universities - Jesicha Sasmita; Nova Mardiana (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
This study aims to understand the effect of flexible work arrangement and work life balance on employee performance, especially lecturers at state universities in Bandar Lampung City. The method used is non-probability sampling, data was collected using convenience sampling techniques to 109 lecturers at state universities in Bandar Lampung City. Validity and reliability tests were carried out by conducting Confirmatory Factor Analysis and Cronbach's Alpha tests. Then the Kolmogorov Smirnov test was carried out to test the data distribution. Hypothesis testing was carried out by looking at the t-value and significant value in multiple regression. The results of the study showed that hypothesis 1, namely flexible work arrangement, has a positive and significant effect on employee performance at state university lecturers in Bandar Lampung City. While hypothesis 2, namely work life balance, does not have a positive and significant effect on employee performance at state university lecturers in Bandar Lampung City. Therefore, agencies need to increase employee commitment, encourage personal work life balance, and strengthen the alignment of individual and organizational goals, in order to create a productive and sustainable work environment.